The MHC class-II HLA-DR receptor mediates bat influenza A-like H17N10 virus entry into mammalian cells - Giotis,E; Carnell,G; Young,E; Ghanny,S; Soteropoulos,P; Barclay,W; Skinner,M; Temperton,N (2019)
Bats are notorious reservoirs of diverse, potentially zoonotic viruses, exemplified by the evolutionarily distinct, influenza A-like viruses H17N10 and H18N11 (BatIVs). The surface glycoproteins [haemagglutinin (H) and neuraminidase (N)] of BatIVs neither bind nor cleave sialic acid receptors, which suggests that these viruses employ cell attachment and entry mechanisms that differ from those of classical influenza A viruses (IAVs). Identifying the cellular factors that mediate entry and determine susceptibility to infection will help assess the host range of BatIVs. Here, we investigated a range of cell lines from different species for their susceptibility to infection by pseudotyped viruses bearing bat H17 and/or N10 envelope proteins. We show that a number of human haematopoietic cancer cell lines and the canine kidney MDCK II (but not MDCK I) cells are susceptible to H17-pseudotypes (H17-PV). We observed with microarrays and qRT-PCR that the dog leukocyte antigen DLA-DRA mRNA is overexpressed in late passaged parental MDCK and commercial MDCK II cells, compared to early passaged parental MDCK and MDCK I cells, respectively. The human orthologue HLA-DRA encodes the alpha subunit of the MHC class II HLA-DR antigen-binding heterodimer. Small interfering RNA- or neutralizing antibody-targeting HLA-DRA, drastically reduced the susceptibility of Raji B cells to H17-PV. Conversely, overexpression of HLA-DRA and its paralogue HLA-DRB1 on the surface of the unsusceptible HEK293T/17 cells conferred susceptibility to H17-PV. The identification of HLA-DR as an H17N10 entry mediator will contribute to a better understanding of the tropism of the virus and will elucidate its zoonotic transmission.